2015
DOI: 10.4236/ajibm.2015.55031
|View full text |Cite
|
Sign up to set email alerts
|

Contractual Governance, Relational Governance, and Firm Performance: The Case of Chinese and Ghanaian and Family Firms

Abstract: Financial performance of firms is a key to long-term survival and profitability. Investors will only invest in firms whose financial performance is creditable; and family businesses are no exception. Perhaps, the performance of family businesses could be attributed to their unique characteristics, which shape their governance. Contractual governance and relational governance are corporate governance structures used to manage the relationships between parties to a transaction and reduce opportunism. Governance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
(47 reference statements)
2
9
0
Order By: Relevance
“…The positive effect on project performance in PPP projects by good relational norms between the public and private sectors has been verified. This finding is consistent with previous studies [40,61,62], which indicate that project performance can also be influenced by relational norms between the public and private sectors, although project performance is stipulated in the concession contracts and is controlled through the implementation of the concession contracts in PPP projects. Contracts are a formal governance mechanism, and relational norms are an informal governance mechanism [81][82][83].…”
Section: Good Relational Norms Improve Project Performancesupporting
confidence: 92%
See 3 more Smart Citations
“…The positive effect on project performance in PPP projects by good relational norms between the public and private sectors has been verified. This finding is consistent with previous studies [40,61,62], which indicate that project performance can also be influenced by relational norms between the public and private sectors, although project performance is stipulated in the concession contracts and is controlled through the implementation of the concession contracts in PPP projects. Contracts are a formal governance mechanism, and relational norms are an informal governance mechanism [81][82][83].…”
Section: Good Relational Norms Improve Project Performancesupporting
confidence: 92%
“…For H1, many prior studies in the field of business have found that good relational norms have positive effects on performance [40,61,62]. As a result, this study tests H1 to verify the effect of relational norms between the public and private sectors on project performance in PPP projects.…”
Section: Hypothesis 3(h3)mentioning
confidence: 81%
See 2 more Smart Citations
“…Stability is achieved through spelling out responsibilities necessary for the fulfilment of joint goals and penalties for not meeting performance requirements. The presence of contracts allows exchange parties to work as promised and restricting opportunistic behaviours because a breach of the predetermined contracts may impose social sanctions such as a loss of participation in future public procurement contracts (Zhou and Xu, 2012;Addae-Boateng et al, 2015). Besides, relational and contractual governance, SMEs need to have good administrative governance so as to be able to respond to the procurement policy requirements.…”
Section: Small and Medium Enterprise Governance Mechanisms And Tendering Capabilitiesmentioning
confidence: 99%